Tumour markers in renal cell carcinoma - Michael, Agnieszka; Dalgleish, Angus (Contemporary Oncology/Współczesna Onkologia, 2002)
Malignant tumours of the kidney account for about 2% of all new cancer cases diagnosed each year. Renal cell carcinoma (RCC) is a resistant tumour that responds poorly to chemotherapy and immunotherapy. One of the reasons why treatment is difficult is lack of independent and reliable prognostic factors. Multiple attempts to discover meaningful prognostic factors that correlate closely with life expectancy, overall survival and response to treatment, have identified a whole new range of molecular markers that may be helpful in diagnosis, as well as treatment selection. The traditional markers such as tumour stage and histological grade belong to the most reliable markers that correlate with survival. Tumour infiltrating lymphocytes and tumoral immune complexes have been tested but they do not follow the clinicopathological data. Some of the acute phase reactants mainly ESR, CRP, ferritin and immunosuppressive acidic protein have been studied for their ability of survival prediction. Only one of them-ferritin turned out to be an independent and significant prognostic marker, however not as good as nuclear grade. The other examples of molecular markers that provide valuable information are genetic alterations in RCC. Some of them i.e. MN/CA9 can identify patients with recurrent disease on the basis of a blood test. Proliferation markers are also promising. Good example here is Ki-67, which correlates with biological aggressiveness in RCC. The next group belongs to adhesion molecules. Here CD44 is of main importance with studies suggesting that CD44 positive tumours are associated with shorter survival. Cadherins are also adhesion molecules that correlate with tumour invasiveness, metastatic potential and poor survival. Molecules that promote plasmin mediated tissue degradation, mainly urokinase-plasminogen activator are thought to be associated with the prevalence of distant metastasis and the development of new metastases postoperatively. Similarly growth factors such as vascular endothelial growth factor and intratumoral microvessel density may be of predictive value. Despite multiple attempts to identify new reliable markers of survival and metastatic potential, the strongest indicators of prognosis are still the tumour size and histological grade of RCC.